2009
DOI: 10.1097/mcg.0b013e3181956e0c
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Endoscopic Data in Juvenile Polyposis Syndrome in Preadolescent Children

Abstract: Colonic polyps in JPS are rarely malignant during the pediatric age period. Our data suggest that the recommended colonic surveillance in children should be modified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…The number of polyps required to define JPS is unclear, with some studies recommending five or more polyps as a criterion [8,12]. JPS is inherited as an autosomal dominant condition with variable penetrance, and a family history is variably reported in 20-75% of patients [1,4,13]. JPS is inherited as an autosomal dominant condition with variable penetrance, and a family history is variably reported in 20-75% of patients [1,4,13].…”
Section: Multiple Polypsmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of polyps required to define JPS is unclear, with some studies recommending five or more polyps as a criterion [8,12]. JPS is inherited as an autosomal dominant condition with variable penetrance, and a family history is variably reported in 20-75% of patients [1,4,13]. JPS is inherited as an autosomal dominant condition with variable penetrance, and a family history is variably reported in 20-75% of patients [1,4,13].…”
Section: Multiple Polypsmentioning
confidence: 99%
“…Children with JPS should undergo surveillance colonoscopy and upper endoscopy with polypectomy every 2 years [18]. Children with JPS often do not undergo genetic testing or upper endoscopy, possibly because there is a lack of awareness among gastroenterologists about the prognostic value of genetic testing and the utility of upper endoscopy in JPS [4]. First-degree, at-risk relatives of patients with JPS should be screened by upper and lower endoscopy after 12 years of age, even when the child is asymptomatic [18].…”
Section: Multiple Polypsmentioning
confidence: 99%
“…Pedunculated polyps are typical in JPS, and a study of children with JPS found a prevalence of only 9.5% for sessile polyps [4]. Given the presence of sessile polyps in our patient, a polyposis syndrome was suspected.…”
Section: Discussionmentioning
confidence: 90%
“…Patients with SMAD4 mutations should be screened for signs of telangiectasias because an overlap syndrome of JPS associated with SMAD4 mutation and HHT has been described [4]. An estimated 15-22% of patients with an SMAD4 mutation may have this JPS-HHT overlap syndrome [5].…”
Section: Discussionmentioning
confidence: 99%
“…For confirmation of the disease, a new technique of endoscopic full thickness resection could be used [83,84]. Polyps can be seen in 6.1% of all colonoscopies in children and 12% of children with rectal hemorrhage [35,85,86]. Rectal bleedings in newborns are common although usually prompt parents to overreact.…”
Section: Colonoscopymentioning
confidence: 99%